COSMOVISÃO INDÍGENA E "NOVOS" DIREITOS: apartes da demarcação da Terra Guarani Morros dos Cavalos - Adriana Biller Aparicio (Universidade Federal do Maranhão, 2012)
This work approaches that the demarcation process of indigenous land's rights is a historical category and a reflection of indigenist's policies during a certain period of time. Nowadays it is a locus of interdisciplinary and politicai struggles. It shows the case of Guarani's Land demarcation named "Morro dos Cavalos" which reveals that the indigenous participation as "subjects" made recognize their territorial rights according to their cosmopolitan view.